Health risks and environmental assessments of heavy metals in road dust of Ramadi, Iraq - Yousif, Yasir M; Mutter, Thamer Y; Hassan, Omar M (Journal of Degraded and Mining Lands Management, 2024)
Air dust is a host medium for potentially harmful substances in atmospheric emissions. Contaminated air with metals causes serious threats to human health. This research aimed to examine the features of road dust pollution and evaluate related heavy metals' health risks. All samples were collected from outdoor environments by including fifty different places in Ramadi using a soft plastic brush. Five heavy metals were evaluated in this study, including nickel (Ni), cadmium (Cd), chromium (Cr), copper (Cu), and lead (Pb). Roadside dust pollution in urban Ramadi streets was assessed using the ecological risk index (RI). Hazard quotient (HQ) and hazard index (HI) calculations were performed for all three exposure pathways (dermal contact, ingestion, and inhalation). The results showed that copper (mean = 49.520 mg/kg) and chromium (mean = 34.742 mg/kg) had the highest heavy metal concentrations, followed by nickel, lead, and cadmium. Even though cadmium was the lowest, however; its ecological risk index was higher than other heavy metals, as cadmium was determined to be higher for dermal adsorption of dust than for inhalation or ingestion in adult people.